A formação leitora de professores de literatura na Região Missioneira - Chassot, Jaqueline (2015)
This study aims to evaluate the reader formation of Literature teachers of public schools along the eleven cities that are part of the 14th Coordenadoria Regional de Educação (CRE), headquartered in Santo Angelo, Rio Grande do Sul. It is discussed here the relationship with reading in school, academic and professional history of participants, noting the process of reader formation and the constitution of their reader identity. The research is based on literature and field studies involving the application of questionnaires to the teachers. Based on the responses of the subjects, it was possible to identify which were the reader experiences that marked his childhood and adolescence and that permeated their academic process, who were their reading mediators, what are their reading habits in the present moment, as well as observing other aspects involved in the relationship between teachers and reading materials, like their teaching practice. With the analysis and interpretation of data, according to the theories of Michèle Petit, Vera Teixeira de Aguiar, Richard Bamberger, Jorge Larrosa, Vincent Jouve, Regina Zilberman, Ezequiel Theodoro da Silva, Arnold Hauser, Ronald Barker and Robert Escarpit, it was found that the reader formation process is influenced by a number of factors that are different for each person. It was found that one of these factors is the contact with the reading before the entry into the school environment, and the family was identified as largely responsible for the stimulus to beginning readers. Also, was possible to verify that all the subjects relied on some reading mediator family member or teacher during their childhood. In addition, it was established that teachers do not read enough and have a fragile relationship with reading, a fact that influences in their teaching practice, making it too traditional. Still, it was concluded that teachers are readers, and coming into contact with different types of reading, especially informative books and best sellers